VÎLCEANU TITELA. 2017. Dynamic Interfaces of Translation, Pragmatics and Intercultural Communication. Craiova: Editura Universitaria Craiova. ISBN: 978-606-14-1282-2, pp. 176. - Simona ȘIMON (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Book review